2022
DOI: 10.14348/molcells.2022.0029
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of ERα by UFM1 Increases Its Stability and Transactivity for Breast Cancer Development

Abstract: The post-translational modification (e.g., phosphorylation) of estrogen receptor α (ERα) plays a role in controlling the expression and subcellular localization of ERα as well as its sensitivity to hormone response. Here, we show that ERα is also modified by UFM1 and this modification (ufmylation) plays a crucial role in promoting the stability and transactivity of ERα, which in turn promotes breast cancer development. The elevation of ufmylation via the knockdown of UFSP2 (the UFM1-deconjugating enzyme in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Studies have displayed that some biomarkers could predict the prognosis of OSCC patients, and inhibiting or promoting their expression could cause tumor growth arrest [2,5,14]. Several studies have reported the association of UFM1 with prognosis in GC, HCC, and breast cancer patients [7][8][9][10]. Currently, the role of UFM1 in OSCC has not been revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have displayed that some biomarkers could predict the prognosis of OSCC patients, and inhibiting or promoting their expression could cause tumor growth arrest [2,5,14]. Several studies have reported the association of UFM1 with prognosis in GC, HCC, and breast cancer patients [7][8][9][10]. Currently, the role of UFM1 in OSCC has not been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…AGING Ubiquitin Fold Modifier 1 (UFM1) is a ubiquitin-like protein that could be coupled to the target protein like ubiquitination through the E1-like activating enzyme UBA5 and E2-like coupling enzyme UFC1 [6]. Previous studies confirmed that the changes in UFM1 expression were related to the progression of gastric cancer (GC), hepatocellular carcinoma (HCC), and breast cancer [7][8][9][10]. For example, the levels of UFM1 were down-regulated in GC tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Histone 4 is also UFMylated following DNA damage to maintain genomic integrity 16,17 . P53, P4HB, and ERα can all be UFMylated to antagonize degradation via the ubiquitin–proteasome pathway 10,18,19 …”
Section: Overview Of the Ufm1 Conjugation Systemmentioning
confidence: 99%
“…16,17 P53, P4HB, and ERα can all be UFMylated to antagonize degradation via the ubiquitin-proteasome pathway. 10,18,19 It has been proposed that most UFMylation components reside in the ER. UFL1, UFSP2, UFBP1, and CDK5RAP3 have all been shown to aggregate in a large protein complex at the cytosolic side of the ER membrane.…”
mentioning
confidence: 99%
“…[ 20 ] Furthermore, by interacting with activating signal cointegrator 1 (ASC1), DDRGK1 regulates ASC1 UFMylation and promotes ER‐positive breast cancer development. [ 21 ] However, DDRGK1 has also been shown to maintain p53 stability and impair the growth of colon cancer via cooperation with UFM1 and covalent modification of p53. [ 22 ] Without further research, it is difficult to fully characterize the function of DDRGK1 in tumors.…”
Section: Introductionmentioning
confidence: 99%